EFFECT OF IRRIGATION WATER SALINITY AND TILLAGE SYSTEMS ON SOME PHYSICAL SOIL PROPERTIES - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The current study investigated the effect of water quality (the salinity of the irrigation water) and Tillage system on some soil physical properties. The experiment was carried out using RCBD with three replicates. wheat was irrigated by three water sources, a  river ,dranege and well waters with electrical conductivities  1.3, 3.5 and 6.9 ds.m-1 respectively and three tillage systems were zero tillage (ZT), conventional tillage (CT) and deep tillage (DT). After harvest, some soil physical properties were evaluated including: bulk density, porosity, penetration resistance, hydraulic conductivity and mean weight diameter. The result showed that the bulk density values were 1.40, 1.44 and 1.47 mg.m-3  for river, derange and well water. while the porosity values were 47.3%, 45.8%  and 43.8%. for river, derange and well water. while the hydraulic conductivity  were 5.13, 4.26 and 4.36 cm.h-1for river , derange and well water. also the result showed that the bulk density values were 1.48, 1.44 and 1.38 mg.m-3 for ZT, CT and DT respectively. while the porosity values were 44.3, 45.7 and 47.8% for ZT, CT and DT respectively. But for the interactions for electrical conductivity with tillage The result showed that the bulk density values were 1.50 mg.m-3  for well water with ZT but decrees value it become 1.34 mg.m-3  for river water with DT. The best type of tillage was conventional tillage as it has the ability to improve properties of soil as well as it helps to reduce.